Accurate short-read alignment through r-index-based pangenome indexing - Varki, Rahul; Rossi, Massimiliano; Ferro, Eddie; Oliva, Marco; Garrison, Erik; Langmead, Ben; Boucher, Christina (Genome Research, 2025)
Aligning to a linear reference genome can result in a higher percentage of reads going unmapped or being incorrectly mapped owing to variations not captured by the reference, otherwise known as reference bias. Recently, in efforts to mitigate reference bias, there has been a movement to switch to using pangenomes, a collection of genomes, as the reference. In this paper, we introduce Moni-align, the first short-read pangenome aligner built on the r-index, a variation of the classical FM-index that can index collections of genomes in O(r)-space, where r is the number of runs in the Burrows–Wheeler transform. Moni-align uses a seed-and-extend strategy for aligning reads, utilizing maximal exact matches as seeds, which can be efficiently obtained with the r-index. Using both simulated and real short-read data sets, we demonstrate that Moni-align achieves alignment accuracy comparable to vg map and vg giraffe, the leading pangenome aligners. Although currently best suited for aligning to localized pangenomes owing to computational constraints, Moni-align offers a robust foundation for future optimizations that could further broaden its applicability.
10.1101/gr.279858.124